Review of Irish patients meeting ST elevation criteria during the COVID-19 pandemic. Issue 2 (3rd August 2021) - Byrne, Luke; Gardiner, Roisin; Devitt, Patrick; Powell, Caleb; Armstrong, Richard; Teehan, Sinead; O'Connor, Stephen
Abstract : Introduction: The COVID-19 pandemic has seen the introduction of important public health measures to minimise the spread of the virus. We aim to identify the impact government restrictions and hospital-based infection control procedures on ST elevation myocardial infarction (STEMI) care during the COVID-19 pandemic. Methods: Patients meeting ST elevation criteria and undergoing primary percutaneous coronary intervention from 27 March 2020, the day initial national lockdown measures were announced in Ireland, were included in the study. Patients presenting after the lockdown period, from 18 May to 31 June 2020, were also examined. Time from symptom onset to first medical contact (FMC), transfer time and time of wire cross was noted. Additionally, patient characteristics, left ventricular ejection fraction, mortality and biochemical parameters were documented. Outcomes and characteristics were compared against a control group of patients meeting ST elevation criteria during the month of January. Results: A total of 42 patients presented with STEMI during the lockdown period. A significant increase in total ischaemic time (TIT) was noted versus controls (8.81 hours (±16.4) vs 2.99 hours (±1.39), p=0.03), with increases driven largely by delays in seeking FMC (7.13 hours (±16.4) vs 1.98 hours (±1.46), p=0.049). TIT remained significantly elevated during the postlockdown period (6.1 hours (±5.3), p=0.05), however, an improvement in patient delays was seen versus the control group (3.99 hours (±4.5), p=0.06). There was no difference seen in transfer times and door to wire cross time during lockdown, however, a significant increase in transfer times was seen postlockdown versus controls (1.81 hours (±1.0) vs 1.1 hours (±0.87), p=0.004). Conclusion: A significant increase in TIT was seen during the lockdown period driven mainly by patient factors highlighting the significance of public health messages on public perception. Additionally, a significant delay in transfer times to our centre was seen postlockdown.